The emergence of eternal life - Hoye, William J. (Cambridge : Cambridge University Press, 2013)
"The question of whether life exists beyond death remains one of the most pertinent of our existence, and theologians continue to address what relevance the answer has for our life in the present. In this book, William J.Hoye uses the phenomenon of emergence - the way higher forms of existence arise from a collection of simpler interactions - as a framework for understanding and defending the concept of eternal life, showing howit 'emerges' fromour present life, our human longing for fulfilment and happiness, and our striving for knowledge of reality. Hoye uses the work of Karl Rahner and Thomas Aquinas to explore questions concerning suffering, the ultimate relevance of morality, and how the fundamental idea of responsibility changes when viewed eschatologically. Contemporary reasons for denying an afterlife are examined critically and extensively. This book will be of great interest to those studying systematic theology, theological anthropology, and Catholic theology"--
Machine generated contents note: 1. Introduction to the question; 2. Motivations for disbelief in a life after death; 3. A justification of the traditional Christian belief in eternal life; 4. Eternal life as the vision of God; 5. The human factor; 6. Life history as the predetermination of eternal life; 7. Sensuality: the resurrection of the body; 8. The emergence of eternal life -- a conclusion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Future life -- Christianity; Catholic Church -- Doctrines; RELIGION / Theology; RELIGION / Christian Theology / Eschatology; Electronic books